2016
DOI: 10.21873/anticanres.11237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spiro-bisheterocycles on Proliferation and Apoptosis in Human Breast Cancer Cell Lines

Abstract: Spiro-bisheterocyclic compounds 2-7 were chemically synthesized. Cell proliferation was assessed by resazurin assay. Annexin V-FITC/ PI apoptosis assays was performed in order to demonstrate apoptotic effects of spiro-bisheterocyclic In breast cancer cell lines.Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to analyze the wild-type p53, MDM2, BAX and caspase 3 gene expression levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Cells were placed in 96-well plates and incubated with the compounds for 24 h. Then resazurin (25 µg/mL) was added to the medium to track their viability. Fluorescence (excitation/emission: 544/590 nm) was recorded for 2 h using a microplate fluorometric reader (Tecan Spark®) [35].…”
Section: Cytotoxicity Evaluation Of the Compoundsmentioning
confidence: 99%
“…Cells were placed in 96-well plates and incubated with the compounds for 24 h. Then resazurin (25 µg/mL) was added to the medium to track their viability. Fluorescence (excitation/emission: 544/590 nm) was recorded for 2 h using a microplate fluorometric reader (Tecan Spark®) [35].…”
Section: Cytotoxicity Evaluation Of the Compoundsmentioning
confidence: 99%
“…Many studies have revealed numerous anti-proliferative and anti-tumor properties of a variety of coumarin and spirocompounds and they were reported to inhibit the proliferation of a number of human malignant cell lines in vitro (9,10,59).…”
Section: Discussionmentioning
confidence: 99%
“…There is also great interest in studying heterocyclic spiro compounds for drug discovery. This is due to their wide range of biological activities, of which mention should made of antioxidant [3], anticancer [4], antidiabetic [5] and antibacterial [6] activities. It is also worth noting that spiro compounds have found application in agriculture as fungicides [7], as well as in materials science as organic semiconductors [8].…”
Section: Introductionmentioning
confidence: 99%